Factors Associated with Blood Pressure and Cholesterol Level in Adolescents: A Survey Study in An Islamic School in Palu City, Indonesia - Nikmah Utami Dewi; Disty Rahmawaty Tahir; Ningsih Wulandari (Journal of Health and Nutrition Research, 2026)
The risk of degenerative diseases, including high blood pressure and high cholesterol levels, can occur at any age. This study aims to explore the relationship between several modifiable factors and blood pressure and cholesterol levels in adolescents. The survey was conducted in one of the Islamic schools in a densely populated area in Palu City using a cross-sectional study design with a simple random sampling technique on 100 respondents aged 15–18 years. Dietary and habitual intake as well as physical activity were collected through a 2x24-hour food recall questionnaire, a qualitative food frequency questionnaire, and an IPAQ questionnaire. Blood pressure and blood cholesterol levels were measured using a digital tension meter and easy touch GCU, respectively. Results indicated that 41 percent of adolescents had elevated blood pressure (>120/80 mmHg)  and 42 percent had high cholesterol levels (≥200 mg/dl), with an average systolic blood pressure of 121 mmHg and cholesterol levels of 199 mg/dL. Only sodium was significantly associated with blood pressure (p = 0.02), and no factors were significantly associated with cholesterol levels after multivariate analysis by including other variables: fat intake, potassium intake, fried and fast-food eating habits, physical activity, and gender (p > 0.05). Further exploration should include additional dietary factors such as saturated fat intake and overall dietary patterns, as well as psychosocial, and environmental influences to help design appropriate nutritional behavior change interventions for adolescents.